Amelioration of influenza virus-induced reactive oxygen species formation by epigallocatechin gallate derived from green tea - Ling Jia-xin; Wei Fei; Li Ning; Li Jin-lin; Chen Liang-jun; Liu Yuan-yuan; Luo Fan; Xiong Hai-rong; Hou Wei; Yang Zhan-qiu (Acta Pharmacologica Sinica, 2016)
Aim: To study whether epigallocatechin gallate (EGCG), a green tea-derived polyphenol, exerted anti-influenza A virus activity in vitro and in vivo. Methods: Madin-Darby canine kidney (MDCK) cells were tested. The antiviral activity of EGCG in the cells was determined using hemagglutination assay and qPCR. Time of addition assay was performed to determine the kinetics of inhibition of influenza A by EGCG. The level of reactive oxygen species (ROS) were determined with confocal microscopy and flow cytometry. BALB/c mice were treated with EGCG (10, 20 or 40 mg·kg−1·d−1, po) for 5 d. On the 3rd d of the treatment, the mice were infected with influenza A virus. Histopathological changes, lung index and virus titers in the lungs were determined. Results: Treatment of influenza A-infected MDCK cells with EGCG (1.25–100 nmol/L) inhibited influenza A replication in a concentration-dependent manner (the ED50 value was 8.71±1.11 nmol/L). Treatment with EGCG (20 nmol/L) significantly suppressed the increased ROS level in MDCK cells following influenza A infection. In BALB/c mice infected with influenza virus, oral administration of EGCG (40 mg·kg−1·d−1) dramatically improved the survival rate, decreased the mean virus yields and mitigated viral pneumonia in the lungs, which was equivalent to oral administration of oseltamivir (40 mg·kg−1·d−1), a positive control drug. Conclusion: The results provide a molecular basis for development of EGCG as a novel and safe chemopreventive agent for influenza A infection.